The Organic Understanding of Social Phenomena:: Part I – The Analogy Between Social Phenomena and Natural Organisms: Its Limits, and the Methodological Point of View for Social Research Resulting Therefrom - Menger, Carl (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this seminal contribution to the development of the methodology of social inquiry in the Austrian School, the author looks at the phenomena of society from the point of view of their organic understanding, from an analogy between these phenomena and the natural organisms, and from the existence of limits to the identification of one with the other. In this way, he derives necessary methodological considerations for the proper understanding of society.